IBM Tivoli storage area network manager : a practical introduction - Brooks, Charlotte; Baus, Michel; Benanti, Michael; Gomilsek, Ivo; Moser, Urs (IBM redbooks., 2003)
Now that you have installed your SAN, how are you going to manage it? This IBM Redbooks publication describes the new product, IBM Tivoli Storage Area Network Manager, an active, intelligent, business-centric management solution for storage resources across the enterprise. IBM Tivoli Storage Area Network Manager provides effective discovery and presentation of SAN physical and logical topologies and provides multiple views of the SAN, including zones. Through its interface, it can be configured to show historical and real-time monitoring of SAN fabric devices. With IBM Tivoli Storage Area Network Manager, you will know what's on your SAN, how the devices are connected, and how storage is assigned to the hosts. If something goes wrong, or new devices are added, the topology display automatically updates to show the changed topology. SAN generated events can be displayed on the manager system, or forwarded to another SNMP manager or Tivoli Enterprise Console. This book is written for those who want to learn more about IBM Tivoli SAN Manager, as well as those who are about to implement it.